The Role of Nursing in Reducing Stigma Toward Patients with Schizophrenia in the Community - Alya Khumaira Zahra (Institute of Accounting Research and Novation (IARN), 2025)
The Role of Nursing in Reducing Stigma Toward Patients with Schizophrenia in the Community Schizophrenia is a chronic mental disorder often accompanied by societal stigma, which can result in social exclusion, discrimination, poor treatment adherence, and reduced quality of life. Nurses, as frontline mental health professionals, play a vital role in addressing stigma through education, therapeutic communication, community outreach, advocacy, and family counseling. Despite this, the contribution of nursing roles to stigma reduction in community settings remains underexplored. This study aimed to examine the role of nursing in reducing stigma toward patients with schizophrenia and to identify factors influencing the effectiveness of nursing-led interventions. A mixed-methods design was employed, involving nurses, patients with schizophrenia, family members, and community members. Data were collected through in-depth interviews, questionnaires, focus group discussions, and observations. Qualitative data were analyzed using thematic analysis, while quantitative data were examined with descriptive and inferential statistics to assess public stigma, self-stigma, and discriminatory behavior. The findings indicate that nursing interventions, including mental health education, therapeutic communication, community outreach, advocacy, and family counseling, were associated with improved public attitudes, reduced self-stigma among patients, and decreased discriminatory behaviors. Nurses’ confidence and competence in stigma reduction also increased, contributing to greater social inclusion and quality of life for patients. Cultural beliefs, community education levels, and institutional support were identified as important moderating factors. In conclusion, nurses play a crucial role in reducing stigma toward patients with schizophrenia, particularly through community-based interventions. Strengthening nursing involvement in anti-stigma programs and providing policy and institutional support are essential for sustainable stigma reduction. This study highlights the importance of nurse-led, community-oriented strategies in promoting acceptance, recovery, and social inclusion for individuals with schizophrenia.